Comparative Study of Language and Communication Skills in Children Conceived by Assisted Reproduction Techniques, In Vitro Fertilization (IVF) and Intracytoplasmic Sperm Injection (ICSI) - Neou, Evangelia; Vlassopoulos, Maria; Lazaratou, Helen; Galanos, Antonis; Papageorgiou, Charalabos (Advances in Social Sciences Research Journal, 2026)
Assisted Reproduction Techniques (ART), such as in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), have been widely applied over the past two decades. However, their association with children’s communication development remains insufficiently explored. This study aimed to compare the language and communication skills of 51 children aged 4–8 years, conceived through IVF, ICSI, or natural conception (control group). Groups were matched by age, gender, and birth order. Assessments included standardized language tests and parental questionnaires evaluating emotional and family factors influencing language growth. Results showed that children conceived through IVF achieved significantly higher scores in vocabulary (p=0.003), grammar, syntax (p=0.002), and sentence structure (p=0.003) compared to ICSI and control groups. No significant differences appeared between ICSI and control groups or in articulation scores. These findings suggest that IVF conception may be linked to enhanced language development, possibly due to richer parent-child communication dynamics.